Grammar Consciousness-Raising Tasks VS Traditional Grammar Lessons for Developing Explicit Knowledge and Accuracy - MOUMENE, Ahmed (Journal of Human Sciences, 2007)
This article attempts to compare the effects ‘Grammar Consciousness-Raising Tasks’ and ‘Traditional Grammar lessons’ on the acquisition of English tenses in terms of gains in explicit knowledge and grammatical accuracy. The study shows that the results of the students who follow the innovative materials overwhelm those who follow the traditional grammar lessons